STUDI ANALISIS STRUKTUR SAYAP DEPAN KUMBANG PADA BERBAGAI KASUS PEMBEBANAN - Aldorado Mahkota, Fatih
Design optimization is one of the most important things in the world of aerospace engineering, because optimization will have an impact on efficiency. One of the optimization methods currently being developed is optimization with a biomimetics approach. In the concept of biomimetics, objects that exist in nature are used as references in making designs. This is based on the assumption about the ability of organisms to adapt to environmental conditions to achieve optimal conditions. One of the objects studied in biomimetics is the rhinoceros beetle. The forewing of the rhinoceros beetle has various advantages in terms of its structure. The wing structure of this beetle is a sandwich structure composite that has a high strengthto- weight ratio. In previous studies, a beetle's forewing geometry reconstruction has been carried out. The beetle's wings were observed using a Scanning Electron Microscope (SEM) and then the observations were used to create a Computer Aided Design (CAD) model. During flight phase of beetles, there are many different types of loads on its wings, so it is important to study the structure of the wings reacting to these loads. This study will discuss about the response of the beetle's forewing structure when given a variation of loading using the Finite Element Method (FEM). The stages in the research started from reconstructing the wing geometry of the original beetle, then simplifying the geometry model and setting up the finite element configuration. In this study, there are many limitations so that it is simplified in several aspects.